Achievements, Challenges, and Perspectives on Nitrogen Electrochemistry for Carbon‐Neutral Energy Technologies. Issue 10 (29th December 2022) - Yang, Xiaoxuan; Mukherjee, Shreya; O'Carroll, Thomas; Hou, Yang; Singh, Meenesh R.; Gauthier, Joseph A.; Wu, Gang
Abstract: Unrestrained anthropogenic activities have severely disrupted the global natural nitrogen cycle, causing numerous energy and environmental issues. Electrocatalytic nitrogen transformation is a feasible and promising strategy for achieving a sustainable nitrogen economy. Synergistically combining multiple nitrogen reactions can realize efficient renewable energy storage and conversion, restore the global nitrogen balance, and remediate environmental crises. Here, we provide a unique aspect to discuss the intriguing nitrogen electrochemistry by linking three essential nitrogen‐containing compounds (i.e., N2, NH3, and NO3 − ) and integrating four essential electrochemical reactions, i.e., the nitrogen reduction reaction (N2 RR), nitrogen oxidation reaction (N2 OR), nitrate reduction reaction (NO3 RR), and ammonia oxidation reaction (NH3 OR). This minireview also summarizes the acquired knowledge of rational catalyst design and underlying reaction mechanisms for these interlinked nitrogen reactions. We further underscore the associated clean energy technologies and a sustainable nitrogen‐based economy. Abstract : A closed nitrogen cycle utilizing electrochemical processes can be established between N2, NH3, and HNO3 . Four essential reactions constitute an overall picture of the nitrogen transformation system, which facilitates the realization of a global carbon‐free green energy network, and remedies the unbalanced natural nitrogen cycle, along with the concomitant environmental crisis.